Reading Across Cultures: Two Stories from Papua New Guinea on Arranged Marriages - Cavallaro, Daniela (Miscelánea: A Journal of English and American Studies, 2005)
After providing a brief sociological introduction to the custom of arranged marriages in Papua New Guinea, this article analyzes two stories by PNG writer Sally-Ann Bagita: “Regret Not” (1973) and “The Reluctant Bride” (1974). The young men and women protagonists of these stories have no choice but to accept a marriage arranged by their families. Focusing particularly on the two female characters, the stories show how each reacts to the same initial situation in very different ways. The article claims that in these two stories Sally-Ann Bagita on the one hand appears to critique the tradition of arranged marriage. On the other hand, however, she also seems to reveal that the problems are not so much in the custom itself, as in the modern, Westernized understanding of it.